To the uttermost parts of the earth : legal imagination and international power, 1300-1870 - Koskenniemi, Martti (Cambridge : Cambridge University Press, 2021)
To the Uttermost Parts of the Earth shows the vital role played by legal imagination in the formation of the international order during 1300-1870. It discusses how European statehood arose during early modernity as a locally specific combination of ideas about sovereign power and property rights, and how those ideas expanded to structure the formation of European empires and consolidate modern international relations. By connecting the development of legal thinking with the history of political thought and by showing the gradual rise of economic analysis into predominance, the author argues that legal ideas from different European legal systems - Spanish, French, English and German - have played a prominent role in the history of global power. This history has emerged in imaginative ways to combine public and private power, sovereignty and property. The book will appeal to readers crossing conventional limits between international law, international relations, history of political thought, jurisprudence and legal history.
Legal imagination in a Christian world : ruling France c. 1300 -- The political theology of jus gentium : the expansion of Spain 1524-1559 -- Italian lessons : ius gentium & reason of state -- The rule of law : Grotius -- Governing sovereignty : negotiating French "absolutism" in Europe 1625-1715 -- Reason, revolution, restoration : European public law 1715-1804 -- Colonies, companies, slaves. French dominium in the world 1627-1804 -- The law and economics of state-building : England c. 1450-c. 1650 -- "Giving law to the world" : England c. 1635-c.1830 -- Global law : ruling the British empire -- A science of state-machines. Ius naturae et gentium as a German discipline c. 1500-1758 -- The end of natural law. German freedom, 1734-1821.
Title from publisher's bibliographic system (viewed on 05 Aug 2021).
Keywords: Grotius, Hugo, -- 1583-1645.; International law -- History; Natural law -- History; Religion and law -- History; Rule of law -- History